Changes in the abomasal contents of pre ruminant calves fed probiotics and kitchen herbs fortified in whole milk: Gastric emptying during Probiotics and Kitchen Herb supplement - RAI, SAROJ; KUMAR, MILAN; BEHARE, PRADIP; MANDAL, SURAJIT; GOGOI, JAYASHREE; DUTTA, T K; MONDAL, MOHAN; SAHU, JYOTIMALA (The Indian Journal of Animal Sciences, 2025)
The aim of the study was to determine curd formation in abomasum of the pre-ruminant calves when fed whole milk fortified with probiotics and kitchen herbs (carom seeds, cinnamon and turmeric) as prophylaxis against calf diarrhoea. Ultrasonographic imaging reveals that these products enhanced clotting process and abomasal emptying. It can be suggested that addition of probiotics and herb mix in whole milk accelerated the process of gastric emptying less than 3 hours (hrs) of feeding.